Practical Approach for Removal of Natural Organic Matter and Defluoridation of Maji ya Chai River Water: Use of Acid Pre-treated Bone Char and Coagulants - Minja, Rwaichi J.A. (Tanzania Journal of Engineering and Technology, 2020)
The removal of natural organic matter (NOM) and fluoride from Maji ya Chai River water (MCRW) using bone char (BC) and coagulants was investigated. Fine BC particles ranging from 0.045 to 0.2 mm were used in a 1 litre half-filled container, stirred at 300 rpm for 60 min followed by addition of a commercial coagulant and allowed to settle for 24 hours to remove NOM. MCRW practicable and affordable defluoridation method for removal of NOM through defluoridation with BC pre-treated with 0.3 N HCl followed by coagulation with Poly-aluminium chloride (PACl) is proposed. Reduction of fluoride from 21 mg/L to 1.7 mg/L was achieved by use of 5 g/L of 0.3 N HCl acid pre-treated BC and 66 mL of 1% PACl per litre of MCRW. The acid pre-treated BC was found to double defluoridation capacity of BC, while adjustment of pH of MCRW with HCl acid to pH 3 has tripled defluoridation capacity of BC. The 0.3 N HCl acid pre-treated BC is preferred to avoid impractical working with acid solution for pH adjustment in households and communities. The treated water pH was within the acceptable portable water range of 6.5 to 8.5. PACl is a preferable coagulant for removal of NOM from MCRW since it is more effective and safer compared to use of alum and zetafloc 703. Keywords: Coagulants, Defluoridation, Fluoride removal capacity, Maji ya chai, NOM removal, Pre-treated bone char.